To complete the calculation of the equation \(x^2 - 6x + 6 = 0\) by completing the square, we follow these steps:
- We start with the expression \(x^2 - 6x + 6 = 0\).
- We need to complete the square on \(x^2 - 6x\). The term to complete the square would be \(\left(\frac{-6}{2}\right)^2 = 9\).
- We rewrite the equation as \(x^2 - 6x + 9 - 9 + 6 = 0\), which simplifies to \((x - 3)^2 - 3 = 0\).
- Rearranging gives us \((x - 3)^2 = 3\).
- Taking the square root gives us \(x - 3 = \pm \sqrt{3}\).
- Finally, solving for \(x\) gives \(x = 3 \pm \sqrt{3}\).
Now we can fill in the blanks:
- Blank space 1: 9
- Blank space 2: -9
- Blank space 3: 3
- Blank space 4: \(\sqrt{3}\)
- Blank space 5: 3
- Blank space 6: \(\sqrt{3}\)
- Blank space 7: 3
- Blank space 8: -\(\sqrt{3}\)
So the completed calculation looks like this:
\[ x^2 - 6x + 6 = 0 \]
\[ \left( x^2 - 6x + 9 \right) - 9 + 6 = 0 \]
\[ \left( x - 3 \right)^2 = 3 \]
\[ x - 3 = \pm \sqrt{3} \]
\[ x = 3 + \sqrt{3} \quad \text{and} \quad x = 3 - \sqrt{3} \]